Nilai Ekonomi Pendayagunaan Konsumtif Kayu Bakar Yang Dimanfaatkan Oleh Masyarakat Sekitar Hutan Lindung Di Gunung Rakutak - Fahriza Luth; Asep Purwanto; Nurwindayani Nurwindayani (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
Firewood is one of forest products which is often used by local people in Mount Rakutak. Firewood has important role in their life. This research is conducted to find out the amount of firewood used in each family in every day and the economic value that it has when it is used by the people in the forest area. The research is located in Resmi Tingal village and Sukarame village and the research uses survey method and the respondents are local farmers who use firewood in the forest area. The result shows that the amount of firewood used by the people is 70.26 m3. and the economic value used by the people in two villages is Rp. 453.126.087 each month or Rp. 386.957 each month for each family.